Triagem de alterações genéticas em indivíduos com diagnóstico clínico de síndrome de Williams-Beuren e com exame da FISH (-) - Batista, Letícia Cassimiro [UNESP] (2024)
Williams-Beuren syndrome (WSB) is caused by a microdeletion in the 7q11.23 region. These deletions are called typical and can be 1.5Mb and 1.8Mb. The phenotype of WSB is characterized by a typical face, specific cognitive profile, and cardiac alterations. Due to this established phenotype, scoring systems have been developed based on the characteristics found in patients in order to aid in the clinical diagnosis and indicate when to make the laboratory diagnosis. This diagnosis can be made by different techniques, such as fluorescence in situ hybridization (FISH), multiplex ligationdependent amplification (MLPA), comparative genomic hybridization on microarrays (aCGH), and next-generation sequencing (NGS) of the exome. This study performed the exome analysis of 22 patients with a clinical diagnosis of WSB and FISH (-). The exome revealed pathogenic and probably pathogenic variants in genes ARID1B, ARID2, NAA15, GIGYF1, MED13L, KAT6B, KAT6A, PTPN11, TRRAP, RFX7, GGCX e GJA1 genes in 10 cases. However, further studies are needed.